2013
DOI: 10.1016/j.chemosphere.2013.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cytotoxicity of pentachlorophenol by perfluorooctane sulfonate or perfluorooctanoic acid in HepG2 cells

Abstract: h i g h l i g h t sPFOS and PFOA could enhance the cytotoxity of PCP to HepG2 cells. PFOS displayed stronger synergistic cytotoxicity with PCP than PFOA. Cytotoxic enhancement might be via strengthening the phosphorylation uncoupling of PCP. PFOS and PFOA might cause membrane disruption and improve the uptake of PCP. a r t i c l e i n f o t r a c tChlorinated phenols and perfluoroalkyl acids (PFAAs) are two kinds of pollutants which are widely present in the environment. Considering liver is the primary toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 43 publications
(50 reference statements)
1
11
1
Order By: Relevance
“…However, under the different conditions of our study, the MTT conversion percentage was increased by PFOA at the doses investigated. Contrary to studies showing that PFOS and PFOA did not increase the proliferation of the cells at concentrations below inhibitory concentrations (Shan et al, 2013;Coperchini et al, 2014), our results revealed that both PFASs were able to increase MTT conversion at concentrations below toxic level. Hormesis is a reproducible and generalizable phenomenon that explains many dose-response relationships (Calabrese et al, 1999).…”
Section: Discussioncontrasting
confidence: 99%
“…However, under the different conditions of our study, the MTT conversion percentage was increased by PFOA at the doses investigated. Contrary to studies showing that PFOS and PFOA did not increase the proliferation of the cells at concentrations below inhibitory concentrations (Shan et al, 2013;Coperchini et al, 2014), our results revealed that both PFASs were able to increase MTT conversion at concentrations below toxic level. Hormesis is a reproducible and generalizable phenomenon that explains many dose-response relationships (Calabrese et al, 1999).…”
Section: Discussioncontrasting
confidence: 99%
“…The principal mechanisms of PCP-induced toxicity appear to be related to the generation of ROS (Shan et al, 2013), which affect the antioxidant system (SOD, CAT, GST, GSH-Px and GSH content) and can cause oxidative damage and lipid peroxidation if oxidative stress overwhelms the defense system. In agreement with this, we observed a decrease in GSH and an increase in MDA content in the PCP-treated groups (Fig.…”
Section: Effect Of Pcp On Antioxidant Enzymes In L Striata Livermentioning
confidence: 99%
“…The elevated levels of these indicators after buprofezin treatment confirmed our hypothesis. Both in vivo and in vitro experiments have also demonstrated that pesticides can reduce the ATP level in liver tissue and HepG2 cells[40,41].…”
mentioning
confidence: 99%